Contextual Sociology Learning Design: Integration of Dick and Carey and Angkringan Pedagogy to Develop Sociological Imagination - Setiawan, Rizki; Yulianto, Yulianto; Hidayat, Sholeh; Asmawati, Luluk; Afrizal, Stevany (Jurnal Pendidikan Progresif, 2025)
Contextual Sociology Learning Design: Integration of Dick and Carey and Angkringan Pedagogy to Develop Sociological Imagination. Objective: This study develops a contextual sociology learning design by integrating the Dick and Carey instructional design model with the angkringan style pedagogy approach. Angkringan pedagogy represents an egalitarian educational framework, grounded in local wisdom, that promotes social reflection and active engagement in discussions surrounding diverse community issues. This method draws inspiration from the daily interactions of Indonesian individuals in angkringan, which serve as friendly and open gathering spaces. The objective is to encourage students' sociological imagination and create a participatory, meaningful, and culturally appropriate learning environment. Methods: The learning design was developed using the Design-Based Case Study (DbCS) technique, involving 82 students in several iterative cycles. Data were collected through participant observation, in-depth interviews, and document analysis, then analyzed qualitatively. Quantitative evaluation was conducted using a rubric to assess scientific articles written by students. The Dick and Carey learning model was modified by integrating elements of angkringan-style discussions, which emphasize equal conversation and social reflection. Findings: The results of the study show that the integration of this approach can increase students' active participation, critical thinking skills, and the ability to develop sociological imagination, especially in linking personal experiences to broader social dynamics. In addition, this design also strengthens equal pedagogical relationships and positively impacts the quality of scientific articles produced by students. Quantitatively, this design improved the average score of students’ scientific articles to 3.79 (categorized as very good) and resulted in the publication of seventeen articles in Sinta 5-indexed national journals and ten in Sinta 6-indexed national journals. Conclusion: Integrating systematic learning design with culturally contextual pedagogical approaches results in an innovative methodology in sociology education. This methodology contributes to forming a reflective academic identity, enhancing research capacity, and developing an inclusive and responsive learning environment to social diversity. This concept strengthens the practice of critical pedagogy in educational institutions and has cross-disciplinary and cross-cultural relevance. Keywords: instructional design, design-based research, dick and carey, angkringan pedagogy, sociological imagination.